2021
DOI: 10.3389/fonc.2021.680615
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Radiotherapy for Patients With Resectable Stage III-N2 Non-Small Cell Lung Cancer: A Systematic Review and Meta-Analysis

Abstract: PurposeFor resectable cases of stage III-N2 non-small cell lung cancer (NSCLC), the best treatment after surgery is still uncertain. The effect of postoperative radiotherapy (PORT) is controversial. Thus, we performed this updated meta-analysis to reassess the data of PORT in stage III-N2 NSCLC patients, to figure out whether these patients can benefit from PORT.MethodsWe conducted searches of the published literature in EMBASE, PubMed, and the Cochrane Library for relevant randomized control trials (RCTs) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
(53 reference statements)
2
10
0
Order By: Relevance
“…With a total of 20 studies included, the results indicated that PORT improved OS in completely resected stage N2 NSCLC, and also showed significant improvements in LRFS and DFS. For completely resected stage N2 NSCLC, PORT may yield better survival outcomes, which is consistent with the meta-analysis results of Zhang et al 5 but different from the recent findings of Lei et al 15 We explored the following points to analyze and explain the survival outcomes with advantages.…”
Section: Discussionsupporting
confidence: 66%
“…With a total of 20 studies included, the results indicated that PORT improved OS in completely resected stage N2 NSCLC, and also showed significant improvements in LRFS and DFS. For completely resected stage N2 NSCLC, PORT may yield better survival outcomes, which is consistent with the meta-analysis results of Zhang et al 5 but different from the recent findings of Lei et al 15 We explored the following points to analyze and explain the survival outcomes with advantages.…”
Section: Discussionsupporting
confidence: 66%
“…Our safety findings are relevant to clinical decision‐making for surgically treatable stage III NSCLC because clinical trials have not documented a clear benefit of chemo‐radiation over chemotherapy only for these patients. 26 We found that, before matching, patients treated with chemo‐radiation had larger tumor size and more extensive nodal status, suggesting that providers tend to select chemo‐radiation for patients with more extensive disease. Similarly, even after matching, chemo‐radiation was associated with a greater rate of noncardiac death, suggesting treatment sorting based on unmeasured lung cancer severity.…”
Section: Discussionmentioning
confidence: 78%
“…Chemo‐radiation is recommended for patients who are nonresectable whereas the benefit of chemo‐radiation is less certain for patients who are resectable. 26 …”
Section: Discussionmentioning
confidence: 99%
“…LNR may also have a considerable role in the use of radiotherapy in the future [33]. The PORT meta-analysis showed no evidence that PORT has obvious benefits [34]. Some studies have even shown that PORT results in a worse prognosis in patients who underwent complete resection for NSCLC [35].…”
Section: Discussionmentioning
confidence: 99%